Metabolome analysis of egg yolk and white following dietary supplementation with Ampelopsis grossedentata extract - Pingping Li; Zhu Li; PanPan Shi; Guifeng Tan; Jianguo Zeng; Peng Huang (Poultry Science, 2024)
ABSTRACT: Eggs are recognized for their rich nutrient profile, providing essential proteins and lipids with notable functional properties. This study examines the effects of incorporating Water Extract of Ampelopsis grossedentata (WEA) into poultry feed on egg quality, focusing on lipid content, choline, L-carnitine levels, and flavonoid compound deposition. Our results show significant increases in essential amino acids, flavonoids, and other bioactive compounds in eggs from WEA-treated hens, suggesting enhanced cardiovascular, antioxidant, and anti-inflammatory benefits. Additionally, we observed elevated levels of choline and betaine in egg yolks, alongside increased L-carnitine content, which may contribute to improved lipid metabolism and reduced cardiovascular disease risk. KEGG pathway analysis revealed upregulation of metabolites involved in critical metabolic pathways, enhancing the nutritional profile of eggs. Flavonoid compounds, traditionally associated with plant-based foods, were also significantly increased, with notable levels of 7, 4′-dihydroxyflavone, daidzein, and glycitein identified in WEA-treated eggs, indicating potential health benefits. These findings suggest that WEA supplementation can produce functional eggs with improved nutritional quality, offering a novel approach to enhancing egg production and meeting the growing demand for functional foods. Further research is needed to fully understand the bioavailability and health impacts of these enriched compounds.